Improvement of disaster coordination preparedness model for soft-target organization - Mohammed Bichi, Abu Bakar (2013)
Disaster coordination preparedness is an approach to protect lives and properties of individuals in the society. The activities are introduced to enable Disaster coordination preparedness Model to analyze and evaluate the vulnerabilities and threats to Soft-target organization, such as common public access area, which include sports areas, parks, and schools etc. it is obvious that more attention is given in recent research focusing mainly on the use of network analysis as a way to examine coordination preparedness in a soft-target organizations. Other factors contributing to the poor Disaster coordination preparedness include Lack of disaster evaluation as a way to examine the vulnerabilities in soft-target organizations and lack of Critical awareness and Adoptive preparedness to the catastrophic situation that would provide effective solution to the soft-target organizations. The aim of this Project is to improve disaster coordination preparedness models for soft-target organizations. The improved model was designed by merging five different models and introducing vulnerability assessment, Critical awareness and Adoptive preparedness components. The improved model was validated and analyzed by four experts’ feedback through distributing of interview questionnaire. The results show that all the experts approved the additional components and the improved model in addressing disaster coordination preparedness for soft-target organization